2020
DOI: 10.21203/rs.3.rs-55610/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

4P Model for Dynamic Prediction of the Covid-19: A Statistical and Machine Learning Approach

Abstract: Introduction: Around the world, scientists are racing hard to understand how Covid-19 epidemic is spreading and growing, thus trying to find ways to prevent it before medications come to pass. Many different models have been proposed so far correlating different factors. Some of them are too localized to indicate a general trend of the pandemic while some others have established transient correlations only.Methods: Hence, in this study, a 4P model has been proposed based on four probabilities (4P) which has be… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…2021 Saudi Arabia Johns Hopkins University Center for Systems Science and Engineering dataset Daily confirmed cases 22 January to 24 July 2020 LSTM 1768.35 - - - [ 43 ] Qatar 735.21 Oman 730.53 Kuwait 456.90 UAE 446.44 Bahrain 320.79 Ghazaly, N., M., et al., 2020 Egypt, Saudi Arabia, Jordan, USA, Spain, Italy, France, Iran, Russia WHO situation reports Daily cases and deaths from 21 January to 2 April, 2020 NAR - - - 2.6521 [ 44 ] Guo, Q. and He, Z., 2021 Global Official WHO data Daily confirmed cases 21 January to 11 November 2020 ANN 3102.9 2090.6 0.9683 - [ 45 ] Hasan, K. T., et al. 2021 Bangladesh Official WHO data and the Institute of Epidemiology, Disease Control and Research of Bangladesh Daily confirmed cases till 3 August 2020 + Government control and people's compliance data + Information of how many people will be in contact with an infected person outside of their home when they move out LSTM 10,368.318 - 1 5.96 [ 46 ] Hazarika, B. B., et al., 2020 Brazil Our World in Data Website Cumulative number of confirmed cases from 11 April to 10 July, 2020 WCRVFL (Using sigmoid or ReLu activation functions) 0.00323 - 0.99975 - [ 47 ] India 0.00147 0.99996 Peru 0.00197 0.99986 Russia 0.0002...…”
Section: Table S1mentioning
confidence: 99%
“…2021 Saudi Arabia Johns Hopkins University Center for Systems Science and Engineering dataset Daily confirmed cases 22 January to 24 July 2020 LSTM 1768.35 - - - [ 43 ] Qatar 735.21 Oman 730.53 Kuwait 456.90 UAE 446.44 Bahrain 320.79 Ghazaly, N., M., et al., 2020 Egypt, Saudi Arabia, Jordan, USA, Spain, Italy, France, Iran, Russia WHO situation reports Daily cases and deaths from 21 January to 2 April, 2020 NAR - - - 2.6521 [ 44 ] Guo, Q. and He, Z., 2021 Global Official WHO data Daily confirmed cases 21 January to 11 November 2020 ANN 3102.9 2090.6 0.9683 - [ 45 ] Hasan, K. T., et al. 2021 Bangladesh Official WHO data and the Institute of Epidemiology, Disease Control and Research of Bangladesh Daily confirmed cases till 3 August 2020 + Government control and people's compliance data + Information of how many people will be in contact with an infected person outside of their home when they move out LSTM 10,368.318 - 1 5.96 [ 46 ] Hazarika, B. B., et al., 2020 Brazil Our World in Data Website Cumulative number of confirmed cases from 11 April to 10 July, 2020 WCRVFL (Using sigmoid or ReLu activation functions) 0.00323 - 0.99975 - [ 47 ] India 0.00147 0.99996 Peru 0.00197 0.99986 Russia 0.0002...…”
Section: Table S1mentioning
confidence: 99%